Factors influencing the sustainability of homestead vegetable production intervention in Rufiji, Tanzania: A cross-sectional mixed methods study. - Killian N Mlalama; Athanasia Matemu; Efraim Kosia; Chelsey R Canavan; Alexandra L Bellows; Mia Blakstad; Ramadhani A Noor; Joyce Kinabo; Wafaie W Fawzi; Honorati Masanja; Dominic Mosha (Public Library of Science (PLoS), 2022)
There is growing evidence that home vegetable gardening interventions improve food security and nutrition outcomes at the family level. Sustainability of many of these community interventions remain a challenge. This study assessed factors influencing the sustainability of homestead vegetable production intervention in Rufiji district, Tanzania, one year after the cessation of external support. This was a community based cross-sectional study using both quantitative and qualitative data collection methods. A total of 247 randomly selected women from households who participated in the homestead vegetable intervention were interviewed using a structured questionnaire. The study held four focus group discussions with women from households that participated in the intervention, and four In-Depth interviews with two extension workers, one community health worker, and one agriculture district officer. Multiple logistic regression for quantitative data and thematic analysis for qualitative data was conducted. About 20.24% (50/247) of households sustained homestead vegetable production for one year after the intervention phased out. Shortage of seeds (adjusted odds ratio = 0.65: CI = 0.46-0.93, p-value 0.018) and either manure or fertilizers (adjusted odds ratio = 1.62: CI = 1.04-2.46, p-value 0.031) were significant factors influencing the sustainability of homesteads vegetable production. In the Focus Group discussions (FGDs) and In-Depth Interview (IDIs), all participating women and extension workers reported high cost of water, destruction from free-grazing animals, agriculture pests and diseases, poor soil fertility, shortage of seeds, and lack of capital affected homestead vegetable production sustainability. Existing individual, community, and system challenges influence the sustainability of external-funded agriculture and nutrition interventions. The study findings underscore the importance of community authorities, scientists, and policymakers in having a well-thought sustainability plan in all promising external-funded interventions.